EFFECT OF LEADER MEMBER EXCHANGE AND PERCEIVED ORGANIZATIONAL SUPPORT ON INNOVATIVE WORK BEHAVIOR OF STAR RATED HOTEL EMPLOYEES - Wijaya, Oscarius Yudhi Ari (Universitas Brawijaya, Indonesia, 2018)
This research aimed to determine the effect of Leader-Member Exchange (LMX) on Innovative Work Behavior (IWB) mediated by Perceived Organizational Support (POS) variable. This research used purposive sampling as a sampling technique. Samples of this study were 243 star rated hotel employees in Surabaya of the non-managerial level. Data collection was done by distributing a questionnaire. All returned questionnaires were analyzed using GCSA-based Structural Equation Modeling. The results revealed that LMX had a positive and significant effect on POS, POS had a positive and significant effect on IWB, and LMX had a positive and significant effect on IWB.